PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD STUDENT TEAMS-ACHIEVEMENT DIVISIONS) TERHADAP HASIL BELAJAR SENI BUDAYA SUB SENI RUPA DI SMPN 1 SUNGAYANG KAB. TANAH DATAR - MASRIALDI, Drs. Wisdiarman, M.Pd, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2014)
This study aims to analyze : whether the implementation of STAD cooperative learning model affects the results of learning the art of fine art sub culture, effect seen from the difference between the learning outcomes of students who are taught through STAD cooperative learning model to the learning outcomes of students who are taught through conventional learning models. This type of research is a quantitative study using a model of experimental, Pretest-Posttest,Control Group Design, with a kind of quasi experiments using two classes, the experimental and control classes. The population in the study were all students at SMPN1 Sungayang totaling 251 students. The population in this study all students at SMPN1 Sungayang, with a sample size of 39 students. Data obtained from the pretest and posttest were then processed into the computer program SPSS PC version 16 and print-outs. Based on the above results suggested to the teacher by using STAD cooperative learning model, the teachers and further research can be used as an alternative to improve the learning activity.Kata Kunci : Model Pembelajaran Kooperatif tipe STAD